Heart condition imaging with the help of hardware and software complex based on the cardiographic equipment on nanosensors - Grigoriev M. G. Mikhail Georgievich (Научно-исследовательская работа молодежи в условиях современного образовательного процесса в вузах России и за рубежом: опыт, традиции, перспективы, 2015)
Заглавие с титульного экрана